How to read a financial report : wringing vital signs out of the numbers - Tracy, John A. (New York : Wiley, 1999)
Steers you quickly and painlessly through the basic accounting concepts and line-by-line explanations of the basic financial statement. Complete with a visual guide that leads you through the intricacies of financial reporting, How to Read a Financial Report shows you how the three essential parts of every financial report - the balance sheet, the income statement, and the cash flow statement - fit together and what it all means to you and your company.
Includes index.
oif 11/03/15
Loans
Keywords: Financial statements; Financial report